2017
DOI: 10.4103/0970-2113.209230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemotherapy on symptom profile, oxidant-antioxidant balance and nutritional status in non-small cell Lung Cancer

Abstract: Background:Lung cancer is associated with an oxidant-antioxidant imbalance that is implicated in tumor progression. However, the association of this imbalance on disease burden and treatment response is unclear. The effect of chemotherapy on oxidative stress, antioxidant status, and nutritional profile in patients with advanced nonsmall cell lung cancer (NSCLC) was prospectively evaluated.Subjects and Methods:Patients with confirmed cytological/histological diagnosis of NSCLC were recruited. Performance status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Levels of MDA variably increased or decreased after first‐cycle of chemotherapy but the overall post‐treatment change in each group was not statistically significant. Mohan et al did not observed any significant change in the levels of MDA at the end of four cycles. In contrast, Gupta et al observed significant increase after three cycles of cisplatin + etoposide which was lesser for responders as compared to non‐responders.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Levels of MDA variably increased or decreased after first‐cycle of chemotherapy but the overall post‐treatment change in each group was not statistically significant. Mohan et al did not observed any significant change in the levels of MDA at the end of four cycles. In contrast, Gupta et al observed significant increase after three cycles of cisplatin + etoposide which was lesser for responders as compared to non‐responders.…”
Section: Discussionmentioning
confidence: 91%
“…[6][7][8][9] Increase in oxidative stress following chemotherapy is reported in one study while no change has been reported in another. 3,10 In contrast, Wakabayashi et al 11 observed significant change in oxidative stress which correlated with response to chemotherapy. Change in inflammatory markers with therapy has also been inconsistently related with response to treatment.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 93%
“…Taherkhani et al [35] have shown that a concurrent significant increase in malondialdehyde levels and a significant decrease in TAS levels were observed after 3 cycles of adriamycin and cytoxan chemotherapy in patients with breast cancer. However, Mohan et al [36] and Krawczyk et al [37] have observed no oxidative stress parameters change was observed after chemotherapy in nonsmall cell lung cancer (NSCLC). And the oxidative stress parameters have the different changes after radiotherapy in different cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced NSCLC diagnosed by cytology, histology and iconography ( 10 ). Patients with complete clinical data.…”
Section: Methodsmentioning
confidence: 99%